STUDY OF NUTRITIONAL VALUE AND PROPERTIES PHYSICAL AND CHEMICAL AND BIOCHEMICAL PLEUROTUS OSTREATUS - Salas De La T., Norma (2004)
Eating mushrooms are an alternative, which provide high biological and nutritional values, because of their proteins and the high level of their macro nutrients.